Promising directions for research on the second-generation immigrants. Issue 13 (3rd October 2019) - Garip, Filiz
ABSTRACT: This article engages with Luthra, Soehl and Waldinger's (2018) Origins and Destinations to consider the future of comparative work on the experiences of second generation immigrants. I highlight the strengths of the book in bringing clarity to existing theoretical debates and in using fitting methods to identify empirical patterns in surveys from New York and Los Angeles. I discuss the future avenues for research inspired by this work that include considering cumulative effects of group-level factors and employing inductive approaches to identifying heterogeneity among second-generation immigrants.